Manajemen Strategi Pondok Pesantren dalam Meningkatkan Kompetensi Santri - Kamila, Ratna; Rahman, Arif; Herman, Herman (Tadbir: Jurnal Manajemen Dakwah, 2022)
This study aims to understand the strategic management of Al-Ma’soem Students Islamic Boarding School in increasing students’ competence starting from formulation, implementation and evaluation of a qualitative descriptive approach as an alternative method of this interviews, observation, and documentation studies. From the research it can be concluded that the Al-Ma’soem Islamic Boarding School students have used a good management strategy. This can be seen from the proven strategy formulation with the formulation of strategies composed of vision, mission, and environmental analysis which are then applied into a strategy. Second, the implementation of the strategy in the ferm of sereval programs and activities arranged by the curriculum and adapted to the needs of students. Third, Strategy evaluation is carried out with two techniques namely program evaluation techniques and outcome evaluation. The final result of this evaluation aim to be able to know the effectiveness of a program that has been designed and implemented in order to improve the competence of students.